Multi-Function CIM Array for Genome Alignment Applications built with Fully Digital Flow - Lanius, Christian; Gemmeke, Tobias (2022 IEEE Nordic Circuits and Systems Conference (NorCAS), 2022)
With the advent of next generation genome sequencing machines, the number of genomic reads has increased in the last few years. The assembly and alignment of the reads to reference genomes is computationally complex: Optimal solutions obtained by solving the approximate string matching problem are computationally infeasible when reference genomes are in the order of 3 billion bases. Modern alignment algorithms perform a preprocessing step, where likely matching regions are computed efficiently and only in that region, a base level alignment is performed. In this paper, we show how sorting and searching in memories can be accelerated, which are key steps in common genome alignment algorithms. We develop a CIM (compute in memory) array out of standard-cells, which is capable of sorting a stream of data, as well as act as a CAM (content addressable memory) and perform multi-word logic operations. We fabricated the 2.6 µm 2 /bit design in a 22nm FDSOI technology, achieving up to 4.28 GB/s throughput and 4.97 nJ/sort at the minimum energy point as a sorter.